2017
DOI: 10.5194/acp-17-9145-2017
|View full text |Cite
|
Sign up to set email alerts
|

Cloud albedo changes in response to anthropogenic sulfate and non-sulfate aerosol forcings in CMIP5 models

Abstract: Abstract. The effects of different aerosol types on cloud albedo are analysed using the linear relation between total albedo and cloud fraction found on a monthly mean scale in regions of subtropical marine stratocumulus clouds and the influence of simulated aerosol variations on this relation. Model experiments from the Coupled Model Intercomparison Project phase 5 (CMIP5) are used to separately study the responses to increases in sulfate, non-sulfate and all anthropogenic aerosols. A cloud brightening on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
1
12
1
Order By: Relevance
“…4, and show some interesting differences from the observational correlations. Contrary to the satellite observations and the findings by Bender et al (2016) and Frey et al (2017), R(L, cloud ) is not significantly positive in any of the ten regions, but actually negative for Iceland, Vanuatu, China, Peruvian and Namibian. R(L, f c ) is also in contrast with observations negative for all regions.…”
Section: Canariancontrasting
confidence: 99%
See 2 more Smart Citations
“…4, and show some interesting differences from the observational correlations. Contrary to the satellite observations and the findings by Bender et al (2016) and Frey et al (2017), R(L, cloud ) is not significantly positive in any of the ten regions, but actually negative for Iceland, Vanuatu, China, Peruvian and Namibian. R(L, f c ) is also in contrast with observations negative for all regions.…”
Section: Canariancontrasting
confidence: 99%
“…The importance of L for cloud in Sc regions, discussed e.g. by Bender et al (2016) and Frey et al (2017), is confirmed by positive correlations R(L, cloud ) in all five Sc regions. R(L, cloud ) is further positive for all regions except with L MAC in the US region.…”
Section: Correlationsmentioning
confidence: 56%
See 1 more Smart Citation
“…Model results have shown large increases in the albedo of clouds with increasing concentration of aerosols which are related to changes in the water content of clouds and in the size distribution of cloud droplets. 125 With respect to the origin of aerosols, anthropogenic sulfate aerosols had greater effect on albedo of clouds than non-sulfate aerosols.…”
Section: Effects Of Aerosols On Uv Radiationmentioning
confidence: 99%
“…Through Model experiments with the Coupled Model Intercomparison Project phase 5 (CMIP5), Frey et al (2017) found that the monthly mean cloud albedo of subtropical marine stratocumulus clouds increased with the addition of anthropogenic aerosols.…”
Section: Introductionmentioning
confidence: 99%